Jamuan hari raya untuk pelajar UTM 1996 [fotograf]
Datuk Ahmad Zaharudin b Idrus - Datuk Prof Dr Mohammad Noor bin Haji Salleh - Prof Dr Abu Azam bin Md Yassin - Prof Dr Md Yusoff bin Abu Bakar - Ismail bin Ibrahim - Mohamed bin Abdullah - Prof Dr Mohd Zulkifli bin Mohd Ghazali - Prof Dr Baharom bin Sanugi - Pro Prof Dr Elias bin Salleh - Prof Ishak bin Abd Rahman - Prof Parid Wardi bin Sudin